2020
DOI: 10.1016/j.molcel.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screens Reveal that Resveratrol Induces Replicative Stress in Human Cells

Abstract: Resveratrol is a natural product associated with wide-ranging effects in animal and cellular models, including lifespan extension. To identify the genetic target of resveratrol in human cells, we conducted genome-wide CRISPR-Cas9 screens to pinpoint genes that confer sensitivity or resistance to resveratrol. An extensive network of DNA damage response and replicative stress genes exhibited genetic interactions with resveratrol and its analog pterostilbene. These genetic profiles showed similarity to the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 103 publications
3
25
0
Order By: Relevance
“…The genome‐wide screen was carried out using the previously described extended knockout (EKO) pooled CRISPR‐Cas9 sgRNA library transduced into an inducible Cas9 NALM‐6 cell clone (Benslimane et al., 2020; Bertomeu et al., 2017) treated with either 0.1% DMSO (v/v) or 20 µM BIBR1532 for 20 days (Figure 1c‐d). Several gene deletions were identified that either buffered cells against (synthetic‐rescue) or sensitized (synthetic‐sick‐lethal, SSL) to treatment with BIBR1532.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genome‐wide screen was carried out using the previously described extended knockout (EKO) pooled CRISPR‐Cas9 sgRNA library transduced into an inducible Cas9 NALM‐6 cell clone (Benslimane et al., 2020; Bertomeu et al., 2017) treated with either 0.1% DMSO (v/v) or 20 µM BIBR1532 for 20 days (Figure 1c‐d). Several gene deletions were identified that either buffered cells against (synthetic‐rescue) or sensitized (synthetic‐sick‐lethal, SSL) to treatment with BIBR1532.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to this study, C16ORF72 / TAPR1 was identified as a hit in human genome‐wide CRISPR‐Cas9 chemogenetic screens for sensitizers to ATR kinase inhibition or hydroxyurea (Hustedt et al., 2019; Benslimane et al., 2020). C16ORF72 / TAPR1 is also a target of miR‐134, a microRNA associated with tumorigenesis and chemo‐resistance (Shuang et al., 2015), and is associated with rare de novo CNVs in autism spectrum disorder (ASD) and schizophrenia (Levinson et al., 2011; Sanders et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PrimPol depleted cells, HU treatment causes a decrease in fork progression, as measured by DNA fibre analysis, which can be rescued by expressing wild-type PrimPol, but not a primase-deficient version of the enzyme ( 132 ). A recent CRISPR screen implicated PrimPol in the response to resveratrol and its chemical analogue pterostilbene ( 142 ). Like HU treatment, Resveratrol also induces comparable dNTP depletion and fork speed decrease, highlighting the drug's ability to cause replication stress.…”
Section: Introduction: the Eukaryotic Dna Replication Machinerymentioning
confidence: 99%